Perancangan Sistem Informasi Persediaan Barang Dengan Metode First In First Out (FIFO) - Andriani Kusumaningrum (Jurnal Ilmiah SINUS, 2011)
Inventories of goods by using First In First Out (FIFO) can be in more control and can know the total cost of existing inventory at any time without having to conduct physical count first.The results of this research is a design information system of merchandise inventory using the First In First Out (FIFO). The design of the system in this research is the context diagram, Design Database comprising eight tables (tables of goods, suppliers of goods into the header, details incoming goods, outgoing goods header, detail stuff out exit, returns the header entry of goods, details incoming goods returns), the scheme menu and input-output design. Keywords : Inventory, First In First Out (FIFO)